Saline water irrigation in agriculture: A case study of mangrove’s salinity tolerance level - S. Suganthi; P. Elavazhahan; P. Manivannan (Innovations in Agriculture, 2022)
Standardizing the saline water irrigation is an important step towards saline water irrigation in agriculture. An experiment was conducted to study the salinity tolerance level of mangrove plant, Lumnitzera racemosa Willd. Under pot culture system. different levels of salinity (0, 100, 200, 300, 400, 500, 600, 700, 800, 900 and 1000 mM NaCl) were imposed on the plants and the variations in mineral content levels was analyzed. Samplings were done on 60, 120 and 180th days after NaCl treatment. From the results it is clear that Mineral constituents such as nitrogen, phosphorus, potassium, calcium and magnesium were increased upto the optimum concentration and there by the tolerance level of this mangrove towards salinity was calculated.